Metrics and provider-based results for completeness and temporal resolution of satellite-based AIS services. (July 2018) - Eriksen, Torkild; Greidanus, Harm; Delaney, Conor
Abstract: Collecting AIS messages from ships by satellites allows for maritime situational awareness, and a wide range of commercial applications, at global and regional scales. This work provides methods and indicators for evaluation of the maritime picture in terms of completeness as well as update intervals of ship tracks. The distribution of the maximum daily time gap between messages of each ship gives good understanding of the freshness of the maritime picture. The distribution is however very skewed, and therefore not well described by the mean and standard deviation. As a single indicator, the median value gives a description of the typical quality of service, whereas percentile levels give insight in the spread. The data used were collected in August 2015 in the Eastern and Southern Africa/Indian Ocean region. Four providers of satellite AIS data were used, plus coastal AIS, making the data set one of the most complete available. Typically 575, 000 AIS messages from 1630 ships were received per day. The median value of the longest time gap in ship tracks was 4.3 h; and the 70- and 90-percentiles were 6.7 h and 19.5 h, respectively. When subsets of all data are used, starting with the data from one provider and adding the others one by one, it is found that the completeness increases asymptotically, but the median of the maximum daily time gap keeps decreasing linearly, showing that additional data in the first place help to track the ships that are already known. Highlights: Performance metrics for satellite-based AIS services are discussed and recommended. The distribution of time gaps between position reports of the same ship is a useful diagnostic. Its median and percentiles give a good description of the typical quality of service. Data from four satellite AIS providers and one terrestrial provider, from August 2015, at equatorial latitudes, was analysed. Typically 575 000 AIS messages from 1 630 ships were received per day. The median value of the longest time gap per day in a ship track was 4.3 hours; the 70- and 90-percentiles were 6.7 and 19.5 hours, respectively.